ASSESSING MANAGEMENT CHALLENGES OF TEACHERS EMPLOYED BY BOARDS IN PUBLIC MIXED DAY SECONDARY SCHOOLS IN KENYA - Owiti, Emmah Awuor; Onderi, Henry; Ajowi, Jack (African Journal of Education and Practice, 2020)
Purpose of Study: The purpose of this study was to assess challenges in managing teachers employed by Board of Management in public mixed day secondary school in Bondo sub-county, Siaya County, Kenya. The objective was to assess challenges principals encounter as they manage teachers employed by Board of Management. Methodology: Sequential research design of mixed method approach was used. Target population was 158. Saturated sampling was used to select the study sample. Data was collected using questionnaire and interviews. Reliability and Validity index were calculated at 0.9 that indicated the instruments were reliable and valid. Responses were coded using Statistical Package for Social Science (SPSS) for windows version 25. Data was analyzed both quantitatively and qualitatively then presented in form of frequency tables. Findings: The Study found out that, principals in public mixed day secondary schools experience recruitment challenges as well as empowerment, team management and career development challenges. These challenges hinder effectiveness of principals' roles as managers of teacher employed by Board of Management. Unique Contribution to Theory, Practice and Policy: The principals can be trained through in-service courses for those who are already serving principals. For the rest, courses that relates to management of teachers employed by Board of Management should be compulsory to anybody who intends to train as a teacher. This will ensure that in future, anybody appointed as a principal is well equipped with knowledge and skills in management of teachers employed by Board of Management. This will reduce the challenges faced by the principals as they manage the teachers employed by Board of Management in their institutions.